Presentation Of Spatial Organization Strategies For Old Texture (Case Study: Kermanshah City) - Joshaghani, Neda; Shafaghi, Sirous; Eghbali, Naser (Opción, 2018)
The present study has been carried out based on field studies and examined the strategies of spatial organization of worn out textures (Case study: Kermanshah City). The results of the study of various aspects of Kermanshah's worn out texture indicate that, despite the severe texture deterioration due to old buildings and the type of material used in them (physical deterioration), the inhabitants of this texture suffer from cultural and social anomalies hardly. According to field studies and numerous observations in the city's worn out texture, it can be concluded that intervention in the texture of this neighborhood should take place emphasizing socioeconomic dimensions (the perspective of synchronization of physical reconstruction and renovation with socio-economic development). Considering the objectives and the research problem, a main hypothesis and three sub-hypotheses are offered for review and analysis. In order to make a correct and logical conclusion of the collected data, the variables are described and then the economic status of the inhabitants of the texture is studied and analyzed. Also, research hypotheses have been tested using t-test, regression test, correlation test, and Friedman ranking test, and a spatial organizing solution has been presented for the worn out texture of Kermanshah City.